THE IMPACT OF WORKPLACE CONFLICT AND STRESS ON PERFORMANCE: EVIDENCE FROM INDONESIA - Ririn Uke Saraswati; Salsabila Sayyidina; Rosdiana (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
Performance is an assessment of the work of employees in carrying out their duties and responsibilities. Under-optimal performance can be caused by conflict factors and work stress experienced by employees. This study analyzes the influence of conflict and work stress on the performance of employees of PT. I.C. Varistor Division Bekasi. The population is 86 Varistor employees, with saturated sampling techniques. The method used is an associative quantitative approach with data collection including observation, filling out questionnaires and documentation, and data is analyzed using SPSS V. 25.  The results of the multiple linear analysis test produced regression equations: Y = 135.487 - 0.392(X1) - 0.693(X2). The results of the partial T test of the conflict had a negative and significant effect with t count (-6.559) > t table 1.989, sig 0.000 < 0.05. Work stress had a negative and significant effect with t count (–12.111) > t table 1.989, sig 0.000 < 0.05. Simultaneous tests showed both negative and significant variables (F count 262.129 > F table 3.11, sig 0.000 < 0.05). The determination coefficient showed that 86% of performance was influenced by conflict and work stress and the rest was influenced by other variables. Companies are advised to conduct periodic evaluations to manage conflicts and work stress in improving employee performance.